Transport properties of two extremely thermophilic species of Thermus - Michaljanicová, D; Kotyk, A; Loginova, L G; Yegorova, L A (Folia microbiologica, 1981)
Thermus flavus and T. ruber grew optimally at 75 and 60 degrees C, respectively, but transport of monosaccharides (D-quinovose) and amino acids (2-aminoisobutyric acid) had optima about 20 degree C lower. Both transports were active, inhibited by 2,4-dinitrophenol but hardly at all by uranyl(2+) ions. Several transport systems are apparently involved with each class of compounds. Preincubation with glucose curtailed subsequent transport severely. Practical cessation of transport below 35 degrees C may be associated with the rather uniform composition of membrane lipids where iso- and anteiso-C15 and C17 acids are practically the only components.
Keywords: Deoxyglucose; Dinitrophenols; aktivní transport; deoxyglukosa; vysoká teplota; Thermus; druhová specificita; Hot Temperature; Monosaccharides; Aminoisobutyric Acids; Species Specificity; monosacharidy; dinitrofenoly; Biological Transport, Active; kyseliny aminoisomáselné; Water Microbiology; Amino Acids; mikrobiologie vody; aminokyseliny